2021
DOI: 10.1097/jom.0000000000002380
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Physicians’ COVID-19 Pandemic Occupational Experiences on Mental Health

Abstract: Objective: To examine the association between a number of negative COVID-19 occupational experiences and probable anxiety, depression, and PTSD among physicians. Methods: Cross-sectional examination of longitudinal registry data consisting of physician personal and occupational well-being. Multivariable logistic regressions were performed to determine the association between negative COVID-19 experiences and outcomes. Results: Of the 620 elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 49 publications
3
32
0
Order By: Relevance
“…However, where the findings diverge somewhat from the quantitative data is in the fact that 50% of the physicians felt that friends and family do not understand the exhaustion caused by their work. Our results are consistent with previous studies that show that married HCWs and those with children reported decreased odds of stress, burnout, anxiety, and depression during the COVID-19 pandemic ( 4 , 29 31 ). In our study, about 75% of the sample was in a relationship, however, the quality of that relationship in terms of support provision is unknown.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, where the findings diverge somewhat from the quantitative data is in the fact that 50% of the physicians felt that friends and family do not understand the exhaustion caused by their work. Our results are consistent with previous studies that show that married HCWs and those with children reported decreased odds of stress, burnout, anxiety, and depression during the COVID-19 pandemic ( 4 , 29 31 ). In our study, about 75% of the sample was in a relationship, however, the quality of that relationship in terms of support provision is unknown.…”
Section: Discussionsupporting
confidence: 93%
“…However, less than a quarter of participants utilized this support. Our results are consistent with other studies that show that both organizational and coworkers' social support reduces the negative impact of occupational stressors and prevents common psychological strains (e.g., anxiety) during the COVID-19 pandemic ( 4 , 35 , 36 ). Moreover, research shows that such support is significant for physicians as it affects self and professional efficacy ( 27 , 28 , 37 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations